2016
DOI: 10.1021/acssuschemeng.6b01319
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Lignin Valorization via Selective Catalytic Technologies and the Tailoring of Biosynthetic Pathways

Abstract: Biomass has received significant attention in the 21st century regarding its ability to become an alternative source of carbon for the production of strategic chemicals and fuels. Although multiple approaches for the selective valorization of biorefinery carbohydrates are known, processes of similar selectivity for the valorization of lignin are scarce, which can be attributed to its heterogeneity arising from its biosynthesis, as well as methods used for its isolation within the biorefinery. This perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 122 publications
0
43
0
Order By: Relevance
“…[15,16,[48][49][50] Due to the wide range of conditions under which sulfite pulping can be conducted and, as ar esult lignosulfonates produced, lignosulfonate structures may vary considerably.H owever,afull lignosulfonate model structure has also been proposed by Matsushita andm ay be found elsewhere. [38,[51][52][53] [38,[51][52][53] …”
Section: Lignosulfonates From Sulfite Spent Liquormentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16,[48][49][50] Due to the wide range of conditions under which sulfite pulping can be conducted and, as ar esult lignosulfonates produced, lignosulfonate structures may vary considerably.H owever,afull lignosulfonate model structure has also been proposed by Matsushita andm ay be found elsewhere. [38,[51][52][53] [38,[51][52][53] …”
Section: Lignosulfonates From Sulfite Spent Liquormentioning
confidence: 99%
“…[39] Additional information on lignin and lignosulfonate structures and modification/biological engineering pathways for the purpose of biorefinery valorization has been covered extensively in recent years. [38,[51][52][53]…”
Section: Lignosulfonates From Sulfite Spent Liquormentioning
confidence: 99%
“…In contrast, the hydrogenolysis of isolated lignin or direct hydrogenolysis of lignocellulosic biomass employing heterogeneous metal‐based catalysts represents an appealing approach for converting lignin into low‐molecular weight compounds; however, such reductive approaches are not new . Early studies in this area by Hibbert and co‐workers using lignin derived from maple and spruce wood meal in combination with a copper–chromium oxide catalyst showed that lignin could be hydrogenolyzed and hydrogenated to furnish 4‐propylcyclohexanol‐based aliphatic alcohols .…”
Section: Figurementioning
confidence: 99%
“…Significant progress has been made on thermochemical approaches for lignin depolymerization such as pyrolysis and chemocatalytic approaches involving the use of heterogeneous and homogeneous catalysts. An extensive overview of lignin valorization methodologies, catalyst developments, and key advances in this field is given in a number of reviews …”
Section: Introductionmentioning
confidence: 99%